1985
DOI: 10.1002/lsm.1900050206
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of myocardial metabolism by laser fluorimetry: Relevance of a test of local ischemia

Abstract: We have developed a hypoxia test by local ischemia, to be performed with a special probe adapted to an in situ NADH laser fluorimeter. Local ischemia is produced by pressurization on the organ surface in an area of approximately 0.2 mm2. In order to assess the method on open-chest rat hearts (ten), we used the following protocol: local ischemia tests (three), global anoxia (100% N2 ventilation), superimposition of local ischemia to global anoxia, and local ischemia tests during the period just prior to death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Fluorescence of mitochondria originates mainly from NADH in the matrix space (22). Arti facts arose with the use of lasers, such as the frequency-doubled nitrogen laser, the helium-cadmium laser, and the 334 nm line of the mercury arc (123), and consisted of (a) greatly increased tissue damage, (b) excitation of pigments whose responses are not correlated with that of NADH and (c) inadequate hemoglobin compensation. Since tissue damage by ultraviolet light decreases at wavelengths above 360 nm, and since a variety of com pensatory procedures are available at 366 nm (108), the 366 nm mercury arc line is recommended.…”
Section: Ultraviolet To Visible Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence of mitochondria originates mainly from NADH in the matrix space (22). Arti facts arose with the use of lasers, such as the frequency-doubled nitrogen laser, the helium-cadmium laser, and the 334 nm line of the mercury arc (123), and consisted of (a) greatly increased tissue damage, (b) excitation of pigments whose responses are not correlated with that of NADH and (c) inadequate hemoglobin compensation. Since tissue damage by ultraviolet light decreases at wavelengths above 360 nm, and since a variety of com pensatory procedures are available at 366 nm (108), the 366 nm mercury arc line is recommended.…”
Section: Ultraviolet To Visible Spectroscopymentioning
confidence: 99%
“…Clinical ly, upon compression of the carotid artery (51), different behaviors of region al cerebral blood volume, hemoglobin oxygen saturation, and cytochrome redox levels were demonstrated between normal volunteers and patients. In these human studies, data from fluorocarbon-substituted cat brains was assumed transferable to humans for the calibration algorithm (120,123,143,168). However, it was recently found that photons migrate over much longer pathlengths in the larger human brain and now the transferability of measure ment on the small animal head is open to question (30).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…(Nighswander-Rempel et al, 2002;Mair, Hammemer-Lercher, 2005). (Renault et al, 1985). В основе метода лежит регистрация изменений клеточной аутофлуоресценции, вызванных восстановлением пиридиновых нуклеотидов во время ишемии (Chance et al, 1962(Chance et al, , 1965.…”
unclassified